Association of depressive symptomatology with problem alcohol use in rural head and neck cancer patients at diagnosis. Issue 6 (2nd November 2022) - Howren, M. Bryant; Seaman, Aaron; Christensen, Alan J.; Pagedar, Nitin A.
Abstract: Purpose: Problem alcohol use is a risk factor for the development of head and neck cancer (HNC) and continued use is associated with poor outcomes; depressive symptoms may be associated with this behavior. Design: Exploratory cross-sectional study examined depressive symptoms as a correlate of self-reported problem alcohol use at diagnosis. Sample/Methods: Multivariable linear regression examined depressive symptoms as a correlate of problem alcohol use in a sample of rural HNC patients ( N  = 249). Findings: Over half (55.2%) of rural patients with potentially problem alcohol use exhibited mild to moderate depressive symptomatology. Regression models controlling for age, cancer site, stage, sex, tobacco use, and treatment modality indicated that depressive symptoms at diagnosis were associated with self-reported problem alcohol use scores at diagnosis (ß = .186, sr 2 = .031, p < .01). Follow-up subgroup analyses demonstrated that depressive symptoms at diagnosis were significantly associated with self-reported problem alcohol use in male patients, those with advanced stage disease, and of older age. Conclusions/Implications: HNC patients should be screened for alcohol use and depression at diagnosis. Access to behavioral health treatment and/or referral options may be lacking in rural areas thus additional ways of connecting rural patients to specialty care should be explored. These may include telehealth and multimodal interventions to address complex behavioral health cases. Additional research in important patient subgroups such as older patients and those presenting with advanced disease is also warranted.